The role of financial technology in improving the efficiency of financial management in the Iraq Stock Exchange - Assistant Techer Ahmed Hassan Ali* (مجلة الدراسات الاقتصادية والادارية)
The research aims to study the impact of financial technology on financial management in the Iraqi Stock Exchange, where financial technology was adopted as an independent variable with its dimensions: (lending, financing, financial control). The importance of the research stems from the fact that it addresses a modern concept that needs further study, and highlights the role of financial technology in enhancing the efficiency of the Iraqi Stock Exchange, which contributes to developing the financial work environment and increasing the attractiveness of the market for local and international investments. The research reached a main conclusion, which is the existence of a positive correlation between the use of financial technology and the improvement of financial management indicators in the market, as it was shown that financial technology enhances the speed and accuracy of trading, which increases the efficiency of financial operations. The research recommended the necessity of investing in developing the digital infrastructure of the market, intensifying training for human cadres on the use of financial technology, in addition to formulating legislation that supports technological innovation and ensures the regulation of financial work in line with global developments. The research community is represented by three banks with shares in the market, where a sample of 200 employees was selected, and the research reached a set of results, including: There is a good correlation between financial technology and the financial management index in the Iraq Stock Exchange, as financial technology contributes to the speed and accuracy of trading in the market.